1905 Ind. Acts 677 - (:unkn) unknown (My University, 1905)
Ch. 169, § 410: Prohibited maliciously or mischievously shooting a gun, rifle, pistol or other weapon, or throwing a stone, stick, club or any other substance at a vehicle. Punishable by imprisonment for 30 days to 1 year and a fine of $10-100.
Keywords: DISCHARGE